2016
DOI: 10.1007/s13659-015-0083-1
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative Triterpenoid Saponins from Leptaulus citroides Baill. from the Madagascar Rain Forest

Abstract: Bioassay-guided fractionation of EtOH extracts obtained from the roots and wood of the Madagascan plant Leptaulus citroides Baill. (Cardiopteridaceae) led to the isolation of ethyl esters of three new triterpenoid saponins (1–3) and the known sesquiterpenoid cinnamosmolide (4). The structures of 1–3 were elucidated by extensive 1D and 2D NMR experiments and mass spectrometry. Compounds 1, 2, and 4 showed moderate cytotoxicity against the A2780 human ovarian cancer cell line with IC50 values of 2.8, 10.2 and 2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Due to the unsustainable harvesting of the bark and roots along with the fact that the natural propagation of WU is problematic, its availability has been declining throughout its nat- Up until now, there have been about 90 compounds isolated from WU, which are mainly composed of sesquiterpenes, flavonoids, fatty acids, lignanamides, and essential oils [25][26][27][28][29]. Some of the compounds isolated from other medicinal plants exhibiting anticancer activity have also been found in WU, such as cinnamosmolide, 6β-acetoxyisodrimenin, ungandensolide, futronolide, warburganal, polygodial, mukaadial, drimenol, and cinnamodial [30][31][32][33][34][35][36].…”
Section: Effect Of Wu Extracts On the Growth Of Human Cancer Cell Linesmentioning
confidence: 99%
“…Due to the unsustainable harvesting of the bark and roots along with the fact that the natural propagation of WU is problematic, its availability has been declining throughout its nat- Up until now, there have been about 90 compounds isolated from WU, which are mainly composed of sesquiterpenes, flavonoids, fatty acids, lignanamides, and essential oils [25][26][27][28][29]. Some of the compounds isolated from other medicinal plants exhibiting anticancer activity have also been found in WU, such as cinnamosmolide, 6β-acetoxyisodrimenin, ungandensolide, futronolide, warburganal, polygodial, mukaadial, drimenol, and cinnamodial [30][31][32][33][34][35][36].…”
Section: Effect Of Wu Extracts On the Growth Of Human Cancer Cell Linesmentioning
confidence: 99%
“…All three new compounds were tested for their toxicity against brine shrimp, and the results indicated that all exhibited moderate activity, with LD 50 values of 0.9, 2.2, and 2.1 µM, respectively. 8) Bioassay-guided fractionation of the ethyl acetate (EtOAc) fraction of the stem bark of Muntafara sessilifolia (Apocynaceae) led to the isolation of four vobasinyl-iboga bisindoles (25)(26)(27)(28) and one 2-acyl monomeric indole (29) alkaloid, along with eight known alkaloids (3-oxocoronaridin hydroxyindolenine, eglandulosine, eglandine, coronaridine, tabernaemontanine, and tabernaelegantines A, B, and D). All the isolated compounds were evaluated for their ability to inhibit the in vitro intraerythrocytic development of the chloroquine-resistant strain FcB1 of P. falciparum.…”
Section: Alkaloidsmentioning
confidence: 99%
“…Although 66 displayed interesting activity, its low therapeutic index (0.788) was discouraging. 26) Bioassay-guided fractionation of EtOH extracts obtained from the roots and wood of the Madagascan plant Leptaulus citroides BAILL. (Cardiopteridaceae) resulted in the isolation of ethyl esters of three new triterpenoid saponins (67-69), together with the known compound cinnamosmolide.…”
Section: Alkaloidsmentioning
confidence: 99%
“…According to an ethnobotanical study, W. ugandensis was used to treat breast cancer, cervical cancer, prostate cancer, skin cancer, throat cancer and intestinal cancer in the rural Greater Mpigi region of Uganda [10]. In addition, a number of studies have documented the cytotoxicity of some compounds in W. ugandensis or in other plant extracts against different types of cancer, including mouth epidermoid carcinoma [5,11,12], ovarian cancer [13], breast cancer [14,15], prostate cancer [16], melanoma [14,17] and glioblastoma [14]. Our previous study showed that WUD exhibited potent inhibitory growth activity against HT-29 CRC cells.…”
Section: Introductionmentioning
confidence: 99%